Water and Sediment Microbial Quality of Mountain and Agricultural Streams. Issue 5 (1st September 2018) - Pandey, Pramod; Soupir, Michelle L.; Wang, Yi; Cao, Wenlong; Biswas, Sagor; Vaddella, Venkata; Atwill, Robert; Merwade, Venkatesh; Pasternack, Gregory
Abstract : Increased public health risk caused by pathogen contamination in streams is a serious issue, and mitigating the risk requires improvement in existing microbial monitoring of streams. To improve understanding of microbial contamination in streams, we monitored Escherichia coli in stream water columns and streambed sediment. Two distinct streams and their subwatersheds were studied: (i) a mountain stream (Merced River, California), which represents pristine and wild conditions, and (ii) an agricultural stream (Squaw Creek, Iowa), which represents an agricultural setting (i.e., crop, manure application, cattle access). Stream water column and sediment samples were collected in multiple locations in the Merced River and Squaw Creek watersheds. Compared with the mountain stream, water column E. coli concentrations in the agricultural stream were considerably higher. In both mountain and agricultural streams, E. coli concentrations in bed sediment were higher than the water column, and principal component analysis indicates that land use affected water column E. coli levels significantly ( p < 0.05). The cluster analysis showed grouping of subwatersheds for each basin, indicating unique land use features of each watershed. In general, water column E. coli levels in the mountain stream were lower than the USEPA's existing water quality criteria for bacteria. However, the E. coli levels in the agricultural stream exceeded the USEPA's microbial water quality criteria by several fold, which substantiated that increased agricultural activities, use of animal waste as fertilizers, and combined effect of rainfall and temperature may act as potential determining factors behind the elevated E. coli levels in agriculture streams. Core Ideas: Watershed land use influences in‐stream pathogen contamination and hence public health risk. The agricultural stream showed higher E. coli concentration than the mountain stream. Increased forest and grassland use showed lower E. coli concentrations in stream water. Increased agricultural land use showed higher E. coli concentrations in stream water. The agricultural stream water column E. coli concentrations far exceeded USEPA recommended values.